Tahap kepimpinan transformasi pengetua di sekolah menengah harian di Negeri Perlis - Ahmad Farid, Karim (2009)
The study intended to examine the level of transformational leadership as practiced by school principals in daily secondary schools at South Zone of Perlis. The dimension of transformational leadership studied in the research were charismatic, inspirational motivation, individualistic consideration and intellectual stimulation. A total of 186 responden were randomly selected teachers from 5 daily secondary school at South Zone of Perlis to participate in the study. A set of questionaire with five Likert scale was distributed in collecting the data which was then analyzed using the Statiscal Package for the Social Science (SPSS) method. The questionaire was adapted from 'Multifactor Leadership Questionaire' (MLQ, 1985). The data was analyzed with descriptive of percentage, mean, frequency, t-test and one way ANOVA. The result indicated that the principals of daily secondary schools at South Zone of Perlis practiced a-medium level of transformational leadership. The study also indicated that teacher's perception by sex, age and service period factors are not related significantly to principal's transformational leadership practiced